Knowledge triumphant : the concept of knowledge in medieval Islam - Rosenthal, Franz, 1914-2003. (Brill Classics in Islam, 2007)
In Knowledge Triumphant , Franz Rosenthal observes that the Islamic civilization is one that is essentially characterized by knowledge ( 'ilm ), for 'ilm is one of those concepts that have dominated Islam and given Muslim civilization its distinctive shape and complexion.' There is no branch of Muslim intellectual and daily life that remained untouched by the all-pervasive attitude towards 'knowledge' as something of supreme value for Muslim being. With a new foreword by Dimitri Gutas.